Adult Education and Social Justice: International Perspectives (Studies on Adult Learning and Education, 2023)
This book investigates the ways in which the social purposes of adult education are (re)interpreted over time, and between the global south and global north. It brings together thirty-seven authors from fourteen countries with extensive experience as academics and/or practitioners in the field. The book is inspired by the work and life of Lalage Bown, a leading proponent of post-colonial and inclusive visions of education for all. Over her long life she worked tirelessly to promote access to basic and higher education for people of all ages and backgrounds: with a deep commitment to striving for greater equality for women. Following an Introduction, the book is structured around four main themes: Adult Education and Social Justice; Decolonisation, Post-Colonialism and Indigenous Knowledge; From Literacy to Lifelong Learning; and, Fostering Excellence, Policy Development and Supporting Future Generation of Adult Educators. The book concludes with reflections on Lalage Bown’s Enduring Legacy.